Comparative analysis of microRNA and messengerRNA expression profiles in plateau zokor testicular cells under reproductive suppression - Yao, Baohui; Kang, Yukun; An, Kang; Tan, Yuchen; Hou, Qiqi; Zhang, Degang; Su, Junhu (Frontiers in Veterinary Science, 2023)
Reproductive suppression is an adaptive strategy that affects the success rate and reproductive efficiency in animals, which in turn affects population continuation and evolution. To clarify the regulatory mechanism of miRNAs in testicular development and spermatogenesis in plateau zokors under reproductive suppression, we analysed the miRNA expression profiles in the testicular cells of non-breeders and breeders during the breeding season. In total, 381 known and 94 novel miRNAs were determined. Compared with that in the breeders, 70 downregulated and 68 upregulated differentially expressed (DE) miRNAs were identified in the non-breeders. We predicted 1670 significant target mRNAs by analyzing the miRNA and mRNA expression profiles. According to the miRNA–mRNA interaction network, the target mRNAs of the DE miRNAs were related to testicular development and spermatogenesis. GO indicate that the target mRNAs were related to testicular development and spermatogenesis. KEGG indicate that pathways of target mRNAs enrichment related to testicular development, spermatogenesis, and energy metabolism. PROK2 was determined as the target mRNA of rno-miR-143-3p. Our study offers a basis for the regulatory mechanisms of miRNAs in testicular development and spermatogenesis in plateau zokor under reproductive suppression and offers a reference for reproductive regulation.